THU0428 Psoriasis Arthritis Is Associated with Periarticular Bone Loss of The Metacarpals. (15th July 2016) - Pfeil, A.; Thodberg, H.H.; Krojniak, L.; Renz, D.M.; Reinhardt, L.; Oelzner, P.; Wolf, G.; Böttcher, J.
Abstract : Background: The BoneXpert is a new Digital X-ray Radiogrammetry method measures the cortical bone thickness of the metacarpals. Objectives: The aim of this study was to quantify cortical bone loss in patients with Psoriasis Arthritis (PsA) and to compare these findings with the PsA modified van der Heijde Sharp Score. Methods: The study includes 104 PsA patients. The BoneXpert method was used to measure the Metacarpal Index (MCIBX ) at the metacarpal bones (II to IV). Additionally, the T-Score of the MCI (T-ScoreMCI ) was calculated. Radiographic severity was evaluated by the PsA modified van der Heijde Sharp Score (Joint Space Narrowing Score and Erosion Score). Results: For the total PsA study cohort the T-ScoreMCI was significantly reduced with -1.289 ± 1.313 SD. The MCI presented a negative correlation to the Joint Space Narrowing Score (r = -0.558; p<0.001) and Erosion Score (r = -0.714; p<0.001) of the PsA modified van der Heijde Sharp Score. In this context, a severity dependent and PsA-related periarticular demineralization as measured by the MCIBX was quantified. The highest reduction was observed for the MCIBX with -28.5% (p<0.01) regarding to the Erosion Score and with -21.1% (p<0.01) for the Joint Space Narrowing Score. Conclusions: Patients with PsA presented also periarticular demineralisation and severity dependent bone loss as measured by the BX using the MCIBX . The BX-parameters seem to function as surrogate marker of radiographic progression in PsA and potentially differentiate between different stages of disease manifestation affecting bone structures. Disclosure of Interest: None declared